Progress on Structured Biosensors for Monitoring Aflatoxin B1 From Biofilms: A Review - Wang, Qi; Yang, Qingli; Wu, Wei (Frontiers in Microbiology, 2020)
Aspergillus is ubiquitous in plenty of crops and can be contaminated in all food chain, including growth, harvest, storage, or processing. Once forming biofilm, Aspergillus would produce a lot of toxins, such as Aflatoxin B1 (AFB1), ochratoxin A, zearalenone, fumonisin, patulin. Among these, AFB1 possesses the highest toxicity and is classified as group I carcinogen to humans and animals by the International Agency for Research on Cancer. Consequently, the proper control of AFB1 from biofilm in foodstuff and feed has been recognized from long past. Moreover, many biosensors have been applied in monitoring AFB1 from biofilm in food. Meanwhile, novel molecular recognition elements and transducer elements have been introduced into the detection of AFB1 in recent years. This review provides an overview of recent advances in biosensors for the determination of AFB1 from biofilm, such as aptasensor, immunosensor and molecularly imprinted polymer (MIP) biosensor. In addition, the current feasibility, limitations, and future challenges in AFB1 determination and analysis are also addressed.